Debiasing job ads by replacing masculine language increases gender diversity of applicant pools - Joyce C. He; Sonia K. Kang (Proceedings of the National Academy of Sciences, 2025)
Job advertisements for jobs in male-dominated fields tend to contain more masculine language, and a commonly proposed intervention to increase gender diversity in applicant pools is to remove this language. In our research, we offer predictions about the broader impact of such interventions on individuals who may not “fit” with traditional masculine identity. Across four multimethod studies ( N = 37,920) spanning both field and lab settings, we demonstrate that a gender debiasing intervention that replaces masculine language in job postings with synonymous gender-neutral language increases application rates among women and men whose self-identities are less aligned with masculinity. Our research highlights that conceptualizing identity incongruence along a continuum can help explain when and why gender diversity initiatives foster the inclusion of a broader group of individuals than initially anticipated.